A dual-antenna global positioning system (GPS) receiver based automated leveling system for tuber harvesters of Ophiopogon japonicus - ZHANG Fangming; LI Jiaming; CHEN Jiasong (浙江大学学报. 农业与生命科学版, 2018)
Ophiopogon japonicus, a kind of local herbal remedies in Zhejiang, is usually grown on rectangular pieces of land. In harvesting season of O. japonicus when a tractor accidentally falls into any furrows, mechanical parts of the tuber harvester hitched behind are prone to break. To solve this problem, an automated leveling system, consisted of a field computer, an electronic control unit (ECU), a dual-antenna GPS receiver, a rope-type sensor, a cylinder, and a hydraulic valve, was developed and tested so that the harvester remained level. The computer got rolling angle of the tractor and displacement of the cylinder in sequence, and then deduced rolling angle of the harvester. The system employed a proportion integration differentiation (PID) algorithm to calculate control quantity of the valve. The experimental results conducted in the fields of O. japonicus showed that the average elevation difference of the left and right points was 1.04 cm, and the standard deviation was 2.39 cm. Therefore, the harvester could remain horizontal all the time, and its mechanical fracture would not happen again.